Urban waterlogging risk assessment in Zhengzhou based on the coupling land surface hazard-pregnant features and underground pipe network operation characteristics - Jinping Zhang; Xuechun Li; Haorui Zhang; Lixin Zhang (Journal of Hydrology: Regional Studies)
Study region: High-tech Zone, Zhengzhou City, Henan, China Province Study focus: Urban waterlogging has become a challenge with increasing urbanization. To enhance the accuracy of regional waterlogging risk assessment, this study proposes a new waterlogging risk assessment method based on the formation mechanism of urban waterlogging process. The method can quantify the risk of land surface hazard-pregnant and underground pipe network operation under different rainstorm scenarios and determine the regional disaster tolerance capacity of urban rainstorm waterlogging. New hydrological insights for the region: Our results show that the southeast and northwest corners of the central dense urban area are most prone to waterlogging, which aligns with actual conditions. In a 1-year rainstorm in the study area, suburban and most densely populated urban areas remain risk-free. However, with the increase of rainfall return period, urban flooding occurs across the area, particularly affecting the central dense urban zone.